Effect of mediator on decontamination of chloroaromatic compounds by using electrochemical method - Abdul Jalil, Aishah; Sundang, Murni; Tajuddin, Norhuda; Akhbar, Suffiyana; Idris, Ani; Triwahyono, Sugeng; Awang Panjang, Noor Fatimah; Tokuda, Masao (2005)

(untitled)
Decontamination of chloroaromatic compounds has been studied under mild conditions by a simple electrochemical reduction method in order to remove chlorine atoms completely from such compounds. Chlorobenzene was used as a model substrate to determine the optimum conditions of the dechlorination, Electrolysis of chlorobenzene in an acetonitrile solution containing tetraethylammonium perchlorate as a supporting electrolyte in a one- compartment cell fitted with a platinum cathode and a zinc anode at a constant current of 60 mA/cm2 was found to be the optimum conditions in this dechlorination. However, complete dechlorination can not be achieved by applying this conditions to dechlorinate 1,3-dichlorobenzene and 1,2,4- trichlorobenzene .Alternative method by adding naphthalene as a mediator in this system was found to solve this problem and as a result, complete dechlorination of such chloroaromatic compounds were achieved to give 100% conversion off the starting materials. This efficient and simple method could be expected and applied to dechlorinate other chloroaromatic compounds in wastewater in order to solve environmental problems.